Primary Communication Disorders in the Nashville Schools: 1979-80 - James Monroe Stewart (Journal of All India Institute of Speech and Hearing, 1970)
The  study  sought  to  determine  the  extent  of service  delivery  for communicative disorders in the Nashville public schools during the academic year 1979-80. Of the  71,662 children enrolled in grades K thru  12,  2,877 children  or 4.01  percent of the population  were receiving services for  communicative  disorders. Of this number,  2,023 or 2.82 percent were primary and 854 or 1.19 per cent were secondary handicaps.  From  these figures, it  was  determined that  70.3 percent of the  service  delivery  was for primary  handicaps  and the remaining 29.3 per  cent for  secondary  handicaps. The  primary  handicaps  of speech, language, and hearing accounted for 83.2,10.6 and 6.2 per cent respectively. Males (63.5 percent) were seen 1.7 times more often than females  (36.5  percent). Quantitatively,  there were  no apparent racial differences. The in-depth analyses indicated  that  blacks had a greater propensity for language disorder than whites while whites had a greater propensity for  hearing  disorders  than blacks.  The  multi- dimensional  scaling  analysis  supported  the  significance  of these  and other  observations.